Avaliação do potencial biológico do extrato da alga e das nanopartículas de ouro biossintetizado com o extrato da alga cystoseira tamariscifolia em modelo experimental de Doença de Crohn - Fontes, Nayana Freire de Almeida (2023)
Inflammatory bowel disease has Crohn's disease and ulcerative colitis as main categories and represents a group of idiopathic chronic inflammatory bowel diseases. Remission of the disease is complex and difficult to achieve, even with pharmacological treatments and recommended therapeutic strategy. In the literature, one can find publications with studies related to the use of the alga Cystoseira tamariscifolia and the effectiveness of its pharmacological activities, among them: neuroprotective, bactericidal, gastroprotective and anti-inflammatory. Nanocarriers, such as Gold nanoparticles, have other important parameters, such as: good direction to the local target, reduced emission and high circulation time. Given the above, the aim of this study was to investigate the anti-inflammatory and antioxidant effect of the algae Cystoseira tamariscifolia (CT) and the use of the algae (CT) with gold nanoparticles (Au@CT) in an experimental model of Crohn's disease. 75 male Swiss mice (Mus musculus) with body mass between 25 g and 30 g were used. For the experimental model, 8% acetic acid (AA) was diluted in distilled water (100ml), and this solution was administered rectally, in a volume of 0.2ml per 10 grams of animal weight. The animals were divided into 8 experimental groups (09 animals/group): saline group, colitis group, dexamethasone group (0.2 ml/30g), CT group (doses: 25, 50 and 100 mg/Kg), Au@CT group (doses: 25, 50 and 100 mg/Kg). After 12 hours of colitis induc- tion and treatments, the animals were euthanized and a 5 cm extension of the colon for morphometric, histological, and biochemical analyzes through macroscopic and mi- croscopic scores, immunohistochemistry for S100 beta and GFAP. Biochemical pa- rameters: myeloperoxidase (MPO), dosage of IL-1beta and TNF-alpha cytokines; bio- chemical parameters: determination of reduced glutathione (GSH), malondialdehyde (MDA) and myeloperoxidase (MPO) activity. Parametric data were analyzed by the test of variance (ANOVA) applied by the Bonferroni test and for the macroscopic and his- tological scores, the Kruskal-Wallis test applied by the Dunn test. It was verified that there is expressive antioxidant and anti-inflammatory activity in the CT seaweed ex- tract, as well as Au@CT and that it does not present toxicity to cell cells in vitro (GON- ÇALVES, A; et al. 2023). Pre-treatment, with Dexamethasone or Au@CT, at doses of 25 and 50 mg/kg, were able to prevent inflammatory aspects such as: ulcer, hypere- mia, edema and colonic prolapse when compared to the Colitis group. The CT 50mg/kg and Au@CT 50mg/kg group had a significant reduction in macroscopic scores, as well as in microscopic scores, when compared to the colitis group. For reduced glutathione, the seaweed CT 50mg/kg and Au@CT 50mg/kg prevented the consumption of GSH and impaired oxidative stress, proven by the reduction in the concentration of MDA when compared to the Colitis group. MPO activity showed a significant reduction in the group treated with CT 50mg/kg and Au@CT 50mg/kg. Pre-treatment, with Dexame- thasone or CT 50mg/kg or Au@CT, at doses of 25 and 50 mg/kg, were able to de- crease the levels of cytokines IL1-beta and TNF alpha, as well as preserving the glial cells of the plexus myenteric.We conclude that the alga Cystoseira tamasriscifolia (CT) and gold nanoparticles biosynthesized with the extract of the alga Cystoseira tamariscifolia Au@CT have a potent biological potential capable of reversing the inflammatory, oxidative processes an exercise neuroprotection of Crohn's disease, in an experimental model induced by acetic acid.